If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + w = 4 Solving 2 + w = 4 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + w = 4 + -2 Combine like terms: 2 + -2 = 0 0 + w = 4 + -2 w = 4 + -2 Combine like terms: 4 + -2 = 2 w = 2 Simplifying w = 2
| 5X-2+3X=9-2X-11 | | -12=9-8x+11x | | 5(5+3m)+5=-45 | | -8x^2+40xy+112y^2=0 | | 3(3x-4)=10x | | 5x+7=21+6 | | 15-3(4w-8)= | | 0.5z=10 | | -3x-3x=40-4 | | 5x+7=7x-9 | | 0.25b=-3 | | 9z=12-21 | | -5x-4(x-8)=34-8x | | 17-(8x-6)= | | 0=-x^2+1.66x-.55 | | 3+0.25x=2 | | 3+2y=21 | | -3(6-4p)+3=-27 | | 3w-5w=18 | | 8x-12=2x+33 | | -2+0.5z=8 | | -7-8a+1=10 | | -4=u-6 | | 8x-63=4x-27 | | 45/1/4= | | 2x+31=4(8x+7)-27 | | 5n-2n=21 | | 8-7=-6b+9 | | 15x+9=12x*27 | | 0.48-4.14x=5.2 | | 5x-4+2x-1=3x+6+2x+1 | | 0.46x+6=1.6 |